PELATIHAN PEMBUATAN KERAJINAN ECOPRINT SEBAGAI POTENSI PENGEMBANGAN KREATIVITAS SISWA DI MTS DDI SALUMBIA - Fahrani Al mahdali; Ikbal Ikbal; Fiansi Fiansi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service program aims to develop students' creative potential through ecoprint craft training at MTs DDI Salumbia, improve life skills, and foster environmental awareness based on the use of environmentally friendly natural materials. This activity was motivated by the limited learning of practical skills that integrate elements of art, creativity, and environmental awareness at the madrasah level. The method used was a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Participants consisted of eighth-grade students selected based on their interests and passion for handicrafts. The training was carried out through stages of introducing the ecoprint concept, selecting and processing natural materials, the motif printing process, and evaluating the work. The training results showed that students were able to process natural materials such as leaves and flowers into ecoprint works that have aesthetic and functional value. In addition, this activity was proven to improve creative thinking skills, fine motor skills, cooperation, and students' awareness of the importance of environmental conservation. Ecoprint training also serves as a learning medium based on life skills and has the potential to be developed into school entrepreneurship activities. Thus, this program can be an innovative educational alternative in shaping the character of madrasa students to be creative, productive, and environmentally aware.